Material and process parameter optimization for dimensional accuracy in Fused Deposition Modeling 3D printing - Rizqi Ilmal Yaqin; Juniawan Preston Siahaan; Mula Tumpu; Bagas Prakoso; Ade Hermawan; Febi Luthfiani; Barokah Barokah; Ahmad Kurniawan (Politeknik Negeri Lhokseumawe, 2024)
The production of complex machine components requires advanced and accurate techniques. Achieving optimal quality through 3D printing involves carefully examining the process parameters. However, many studies have not thoroughly explored the impact of these parameters on parts produced using Fused Deposition Modeling (FDM) 3D printing. This study evaluates how process parameters and material variations affect the dimensional accuracy of printed parts. The study focuses on input variables such as material type, infill density, infill pattern, and raster angle. Using the fractional L9 Taguchi method, the optimal settings identified were PLA+ material, 80% infill density, an infill grid pattern, and a 0° raster angle, resulting in a 1.39%-dimensional deviation and an S/N ratio of -3.29 dB. ANOVA analysis reveals material type as the most significant factor, contributing 49.81% to performance. These findings, complemented by statistical analyses, can guide decision-making in industrial applications and serve as a reference for selecting FDM 3D printing settings related to dimensional accuracy to print components in the industry.